Reduced aortic lesions and elevated high density lipoprotein levels in transgenic mice overexpressing mouse apolipoprotein A-IV. - Cohen, R D (1997)
Transgenic mouse lines carrying several copies of the mouse apo A-IV gene were produced. Lipoprotein composition and function, and aortic lesion development were examined. Apo A-IV levels in the plasma of transgenic mice were elevated threefold compared with nontransgenic littermates on a chow diet, and sixfold in mice fed an atherogenic diet. Plasma concentrations of total cholesterol, HDL cholesterol, triglycerides, and free fatty acids were similar in transgenic and control mice fed a chow diet. However, with the atherogenic diet, male transgenic mice exhibited significantly higher levels of plasma triglycerides (P < 0.05), total cholesterol (P < 0.01), HDL cholesterol (P < 0.0001), and free fatty acids (P < 0.05), and lower levels of unesterified cholesterol (P < 0.05), than nontransgenic littermates. Expression of the apo A-IV transgene had a protective effect against the formation of diet-induced aortic lesions, with transgenics exhibiting lesion scores of approximately 30% those seen in control mice. HDL-sized lipoproteins isolated from transgenic mice fed the atherogenic diet promoted cholesterol efflux from cholesterol-loaded human monocytes more efficiently than comparable lipoproteins from nontransgenic counterparts. Plasma from transgenics also exhibited higher endogenous cholesterol esterification rates. Taken together, these results suggest that apo A-IV levels influence the metabolism and antiatherogenic properties of HDL.